ADENOMA PLEUMORFIK PADA PALATUM (laporan kasus) - Budi Sumarsetyo (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2010)
Pleumorphic adenoma is adenoma of salivary gland. I'ts a mix tumor which consists of some component such as epithel, myoepithel, asnd mesenchyme. Pleomorphic adenoma is benigna tumor that grows slowly and doesn't grow at certain size. However it can be turned into malignant and become carcinoma. This tumor appears as single mass, solid, elastic, cirular, mobile and painless. Pleumorphic adenoma in major salivary gland often occur in the parotid gland, but in the minor salivary gland it often occur on the palatum and upper lip. Etiology of this tumor is not clear, but it can be caused by enviroment and genetic factor. Surgical treatment for Pleumorphic adenoma has a good prognosis.. Two Pleumorphic adenoma cases are reported in the Dr.Soebandi hospital, Jember. 53 years old female and 48 years old maleb suffering Pleumorphic adenoma on the palatum moleand palatum durum. Surgery treatment were done for that patients and the result is good